Case Report: Primary Aldosteronism Due to Bilateral Aldosterone-Producing Micronodules With HISTALDO Classical and Contralateral Non-Classical Pathology - Chen, Yi-Ju; Peng, Kang-Yung; Chueh, Jeff S.; Liao, Hung-Wei; Hsieh, Tsung-Yi; Wu, Vin-Cent; Wang, Shuo-Meng (Frontiers in Endocrinology, 2022)
Background: Non-classical multiple aldosterone-producing micronodules/ nodules (mAPM/mAPN) could be the pathogenesis of primary aldosteronism (PA). The co-existence of mAPM with adenomas harboring somatic mutations has not previously been reported. Methods: We presented a PA patient with bilateral mAPM and concomitant autonomous cortisol secretion (ACS). Results: A 46-year-old Taiwanese woman presented with hypertension, hypokalemia, and bilateral adrenal adenomas. A 1 mg low-dose dexamethasone suppression test showed elevated morning serum cortisol. An adrenal vein sampling (AVS) suggested a left-sided lateralization of hyperaldosteronism. A right partial adrenalectomy and a left total adrenalectomy were performed. The patient showed biochemical and hypertension remission after the operation. This patient had bilateral mAPM with concomitant ACS, a right histopathologically classical PA adenoma, and a left non-classical PA adenoma. The right adrenal adenoma showed CYP11B1-negative and CYP11B2-positive staining, and harbored the KCNJ5-L168R mutation. The left adrenal adenoma showed CYP11B1-positive and CYP11B2-negative staining, and harbored the PRKACA-L206R mutation. . Conclusion: In a PA patient with concomitant ACS, bilateral APM could coexist with both histopathologically classical and non-classical PA adenomas, each with different somatic mutations. The presence of ACS could lead to the misinterpretation of AVS results.